Sustainability of digital collections for Nigerian academic libraries: An exploration of conception, indicators for fulfillment and accrued benefits - Yakubu, Hajara; Abdullah, Noorhidawati; Kaur, Kiran (Malaysian Journal of Library and Information Science, 2022)
Collection management in libraries has evolved alongside the developments of the new technologies effecting libraries. As digital collections are increasingly becoming the preferred resources by remote library users, librarians are faced with the challenge of proving a seamless continuation of efficient accessibility to these digital collections over time. This study aims to explore librarians’ understanding of the sustainability of digital collections, the criteria for its fulfilment, and their perspectives on the accrued benefits of the practice. The study employs a qualitative approach, with purposive sampling of 25 experienced librarians and library ICT personnel from three federal universities in Nigeria. Semi-structured interviews and focus groups discussions were used in the data collection. Result reveals that the academic librarians are insightful about what it means by sustaining digital collections in their respective universities. The themes generated are the provision of access, digitization, preservation, task functions, and services. The criteria to be achieved for the sustainability of digital collections, includes skilled manpower, professional development, defined roles, ICT infrastructure, funding, and maintenance. The movement for sustaining digital collections in academic libraries in Nigeria will benefit the library’s reputation, improve the services offered, aid in the preservation of the collections, promote resource sharing, and reduce time and cost. The study suggests that academic librarians need ongoing training to keep them abreast of the latest technology for crucial understanding in a bid to sustain their digital collections.